Electrocardiogram Abnormalities Suggest Aberrant Cardiac Conduction in Huntington's Disease. Issue 3 (11th April 2018) - Stephen, Christopher D.; Hung, Judy; Schifitto, Giovanni; Hersch, Steven M.; Rosas, H. Diana
Abstract: Background: There is increasing evidence that the effects of Huntington's disease (HD) extend beyond the central nervous system. In particular, significant cardiac dysfunction has been described in transgenic mouse models and suggested in symptomatic patients, in whom cardiac involvement could provide an independent risk for sudden cardiac death. Methods: Standard 12‐lead electrocardiograms (ECGs) obtained at screening from 590 early symptomatic (Stage 1 and 2) HD patients participating in a multi‐site Phase III study were analyzed. Results: Evaluating only those ECGs in individuals not on medications or with potentially contributing medical conditions, the prevalence of bradycardia was 28.3% (marked in 5.8%), prolonged QRS 4.9%, intraventricular conduction delay 3.4%, right bundle branch block 1.3%, and QTc prolongation 3.7%. Conclusion: Significant cardiac abnormalities, characterized primarily by conduction abnormalities, were found in a larger than expected number of patients. Abnormal intraventricular conduction may lead to increased risk for arrhythmia and may be compounded by prescription of QT‐prolonging medications.